2014
DOI: 10.1007/s00396-014-3410-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spontaneous wetting and drop impact dynamics of aqueous surfactant solutions on hydrophobic polypropylene surfaces: scaling of the contact radius

Abstract: In this paper, we comparatively investigated the spontaneous wetting and the impact dynamics of surfactantladen drops on hydrophobic polypropylene surfaces. We used the organic anionic surfactant sodium dodecyl sulfate (SDS) and two silicone-based nonionic surfactants, one of which was a so-called superspreader. The wetting dynamics during spontaneous spreading could be divided into an early inertiadominated stage and a later viscosity-dominated stage. Both could be described by power laws with different expon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 48 publications
(84 reference statements)
2
16
0
Order By: Relevance
“…This first criterion sets the lower limit in Weber number for pancake bouncing, which we observe on our surface architecture to be at 7 We  . The second necessary condition for pancake bouncing is that the time for the liquid to penetrate and 9 empty the macro-texture, t  , matches the time the droplet takes to spread out to its maximum diameter, max t , which means that the ratio of these two times 20 We  we observe partial rebound on the macro-textured surfaces and the S-PTFE surface (see Figure S3). two protruding macro features in the square lattice, 0.4…”
Section: Surface Identifiermentioning
confidence: 75%
See 3 more Smart Citations
“…This first criterion sets the lower limit in Weber number for pancake bouncing, which we observe on our surface architecture to be at 7 We  . The second necessary condition for pancake bouncing is that the time for the liquid to penetrate and 9 empty the macro-texture, t  , matches the time the droplet takes to spread out to its maximum diameter, max t , which means that the ratio of these two times 20 We  we observe partial rebound on the macro-textured surfaces and the S-PTFE surface (see Figure S3). two protruding macro features in the square lattice, 0.4…”
Section: Surface Identifiermentioning
confidence: 75%
“…The indentations were included in the surface design to allow for a mechanically stable architecture with short protrusions while still providing a large available surface area to store surface energy during droplet impact. Here we found that for 20 We  these indentations simultaneously increase the risk of pinning during the droplet retraction stage, which slows down the receding liquid within the macro-texture and can result in droplet breakup in the macro-texture (see Figure S3 for side-view image sequences at 20 We  on the S-HFS and the T-HFS surface). To facilitate dewetting and limit pinning events, it is important to reduce the presence of sharp edges, thus preventing liquid from remaining in the texture.…”
Section:  mentioning
confidence: 77%
See 2 more Smart Citations
“…However, the dynamic wetting of multicomponent liquids, like surfactant solutions, is less understood. In recent years, an increasing amount of research has been done on this topic [3,[20][21][22][23][24][25][26][27]. Surfactant molecules absorb at the interface and change the interfacial tension [28].…”
Section: Introductionmentioning
confidence: 99%